Periodic solutions of “predator–prey” systems with continuous delay and periodic coefficients - Borzdyko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We prove the existence of positive ω-periodic solutions for some “predator–prey” systems with continuous delay of the argument for the case where the parameters of these systems are specified by ω-periodic continuous positive functions.